Surface Properties of Aqueous Solutions of 2-Hydroxypropylmethacrylate - Azizinezhad, Fariborz (Asian Journal of Chemistry, 2010)
Some monomers can decrease surface tension and critical micelle concentration. In this study, the effect of 2-hydroxypropylmethacrylate on stability of emulsion system and its distribution into toluene water system, surface tension, surface entropy, surface enthalpy and halfdecay time with sodium lauryl sulphate as an anionic emulsifier has been investigated. Results showed that the surface tension and critical micelle concentration in the presence of monomers decreased. The stability and homogeneity of the system in the presence of monomers increased.